Energy Band Structures of Group IV Elements Including Fullerene, Graphite, and Diamond Using the Quantum Quantitative Model (JOURNAL OF ADVANCES IN PHYSICS, 2025)
The crystalline accommodation law quantum quantitative model (CALQQM) gives the exact relation between the crystal structure and the electronic energy band structure. In addition, it could explain successfully the superconductivity at room temperature, energy levels, and work functions of materials. This model opens the way to reconsider the energy band structures of all crystalline materials according to it. Therefore, we aim to use CALQQM to determine the electronic band structures of group IV elements including their allotropes such as fullerene, graphite, diamond, and α-Sn. Here, we show a great success in determining the band structures of these elements. CALQQM predicted with high accuracy their electronic properties such as work functions, energy gaps, and spectra in a good agreement with experimental results. A perfect agreement between the calculated value (4.69 eV) and experimental value (4.69 eV) of the work function of fullerene 60 was obtained.